PELAYANAN SERTIPIKAT HAK ATAS TANAH DI KANTOR PERTANAHAN KABUPATEN TUBAN (STUDI PENINGKATAN KINERJA PELAYANAN SERTIPIKAT HAK ATAS TANAH MELALAUI PROYEK OPERASI NASIONAL AGRARIA (PRONA) DI KANTOR PERTANAHANKABUPATEN TUBAN) - Efendi, Kacung (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
Prona is an activity organized by the government in the land sector in general and in thefield of land registration in particular, in the form of land pensertipikatan implementedsimultaneously together (bulk) and the settlement of land disputes that are strategic. Thepurpose of this study is to analyze the performance of the service certificate of landrights through the Land Office Prona in Tuban, as well as to analyze the factors that ledto the performance of the service certificate of land rights through the Land OfficeProna in Tuban. The survey results revealed that the implementation of theImplementation of Public Services On Certificate of Land Through the Land OfficeProna in Tuban has appropriate technical guidelines (Juknis) BPN. The ten principles ofservice stipulated in a decree of the Minister of State Apparatus No. 63 / KEP / M.PAN/ 7/2003 on General Guidelines for the Implementation of Public Service. Not optimalperformance of the public service of the Land Office Prona in Tuban due to lack ofhuman resources, lack of support equipment, as well as the lack of socialization to thecommunity about Prona. In implementing the program Prona Tuban District LandOffice are the problems / obstacles both from the physical aspect, the community, staff,and the financial aspect.Keywords: Services, Prona, Rights to Land, Tuban